(untitled) (Damascus University Journal of arts and humanities sciences, 2025)
This study aimed to know the effect of teaser advertisements on the purchasing behavior of Damascus University students, by conducting a field study on outdoor teaser advertisements. The study was conducted on a sample of 231 male and female students from the University of Damascus, 137 female and 94 male students, as its results showed that the majority of the researched sample, by more than 77%, are exposed to teaser advertisements. The results of the study also showed that the majority of the sample - who are exposed to teaser advertisements - with a rate of more than 85%, accept to follow teaser advertisements, either out of need and satisfaction or out of ambiguity and curiosity. According to the results, a large percentage of the study sample - which is exposed to teaser advertisements - exceeds 60%, they trust the content provided by teaser ads, while nearly a quarter of this sample does not trust the content they provide. According to the results of the study, the majority of the study sample - which is exposed to teaser advertisements - exceeds 65% the teaser advertisements prompted them to decide to buy the products they promote, while 22.6% of this sample said otherwise. 70% of the study sample - who are exposed to teaser advertisements - see teaser advertisements as an effective way to promote products and services compared to other means, while 23.56% of this sample see otherwise.